DEAD‐Box Helicase 17 exacerbates non‐alcoholic steatohepatitis via transcriptional repression of cyp2c29, inducing hepatic lipid metabolism disorder and eliciting the activation of M1 macrophages - Ning Deng; Jie Jin; Yuanyuan Fang; Pengcheng Du; Chaoyi Yuan; Jin Chen; Qibo Huang; Kun Cheng; Jie Mo; Lei Xu; Hui Guo; Mia Jiming Yang; et al. (2024)
Our study was to elucidate the role of RNA helicase DEAD-Box Helicase 17 (DDX17) in NAFLD and to explore its underlying mechanisms.